The Antibacterial Activity of Erythrocytes From Goose (Anser domesticus) Can Be Associated With Phagocytosis and Respiratory Burst Generation - Yang, Youcheng; Chen, Jiajun; Lu, Linqing; Xu, Zizheng; Li, Feng; Yang, Minxuan; Li, Jun; Lin, Li; Qin, Zhendong (Frontiers in Immunology, 2022)
In the lumen of blood vessels, there are large numbers of erythrocytes, which are ap-proximately 95% of the total blood cells. Although the function of erythrocytes is to transport oxygen in the organism, recent studies have shown that mammalian and tel-eost erythrocytes are involved in the immune response against bacterial infections. However, the immune mechanisms used by avian erythrocytes are not yet clear. Here, we demonstrated that erythrocytes from goose have the ability to phagocytose as well as conduct antimicrobial activity. Firstly, we revealed the phagocytosis or adhesion activity of goose erythrocytes for latex beads 0.1-1.0 μm in diameter by fluorescence microscopy, and scanning and transmission electron microscopy. The low cytometry results also proved that goose erythrocytes had a wide range of phagocytic or adhe-sion activity for different bacteria. Followed, the low cytometry analysis data further explored that the goose erythrocytes contain the ability to produce reactive oxygen species (ROS) and inducible nitric oxide synthase (iNOS) in response to bacterial stimulation, and also up-regulated the expression of NOX family includes NOX1 and NOX5. Finally, we also found that goose erythrocytes showed a powerful antibacteri-al activity against all the three bacteria, meanwhile the stimulation of three kinds of bacteria up-regulated the expression of inflammatory factors, and increased the pro-duction of antioxidant enzymes to protect the cells from oxidative damage. Herein, our results demonstrate that goose Erythrocytes possess a certain phagocytic capacity and antioxidant system, and that the antimicrobial activity of erythrocytes can oc-curred through the production of unique respiratory burst against foreign pathogenic bacteria, which provides new clues to the interaction between bacteria and avian erythrocytes.